Faszyzm a prawo. Głos w dyskusji - Sondel, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
Adolf Hitler, who after the unsuccessful Munich Putsch of 1923 had changed his tactics and gained power by legal means after being appointed the Chancellor of the Reich on the 30th of January 1933 by the President Paul von Hindenburg, began the implementation of his party’s program but at the start of his rule he attempted to maintain a pretense of legalism. However, over time, he progressively attached less importance to this guise which was made possible by the declaration — by the President’s decree for the protection of the nation and state February 28, 1933 — of the state of emergency which in fact was never formally revoked. The above-mentioned decree was for Hitler an extraordinarily useful instrument in his pursuit for incapacitation of state’s legal institutions and for seizure of dictatorial power. It was also observable in the realm of law in which there happened a Draconian aggravation of criminal penalties, a rejection of the most fundamental rule of legalism concerning the inadmissibility of the retroactivity of legal rules, a creation of Popular Tribunals and special courts, an extermination — in the majesty of law — of Jewish population and of feeble-minded persons, etc. In the sphere of civil law the interest of the state was considered to possess an absolute priority over individual rights which ultimately led to the disappearance of the boundaries between public and private law. The Italian Fascism was comparatively less harsh in its policies. Though it also accepted the employment of terror against political opponents as a way of governing, it never applied this method on as large a scale as it was done in the Third Reich. Benito Mussolini, the leader of the Fascist Italy, openly expressed his disapproval of Nazi’s undertakings towards Polish state in 1939; he also vigorously attempted to secure a release of the Jagiellonian University professors arrested and imprisoned on the 6th of November 1939 during Sonderaktion Krakau. At the same time, the Italian Fascists extolled the achievements of the ancient Rome — also in the field of law — which was a complete and utter anathema to Nazis who opposed Roman law on the most fundamental level. The fight against this law was considered by the latter to be one of their essential political principles, as evidenced by the 19th point of the NSDAP program adopted on the 24th of February 1920. This position of German ideologues also found its reflections in literature, particularly in a short story written by Louis Aragon and titled Roman law has ceased to exist and in poetic works of Mieczysław Jastrun, which anyway provide an excellent commentary on the abovementioned doctrinal propositions of the Nazi party.
Keywords: faszyzm; Hitler, Adolf (1889-1945); prawo; sankcje; stan wyjątkowy